Managing the end of life in COVID patients. The role of palliative care in emergency departments during the pandemic - Sena, Barbara; De Luca, Enrico (Frontiers in Sociology, 2022)
Managing Covid-19 patients has been an extremely difficult and dramatic task, especially for emergency departments during the strongest waves of the pandemic in Italy. Medical staff and health professionals were redeployed from their work setting to covid units; many were overwhelmed by the deaths of so many patients in a very short time. This work aimed to explore palliative care health professionals' and physicians’ perceptions of end-of-life care management in covid units during the first two waves of the pandemic in Italy. Qualitative data was collected through 24 semi-structured in-depth interviews. The participants were palliative care medical and health professionals redeployed, or in a supporting role, covid units from the most affected areas of northern and central Italy. The interview questions were focused on four thematic areas concerning different aspects of the role and responsibilities of the palliative care specialist (physician and healthcare professional). A brief presentation of the main sociological literature on end-of-life management in hospital contexts will be firstly presented and discussed to offer a theoretical frame. Subsequently, some of the most significant results that emerged from our research will be illustrated concerning the role played by palliative care professionals during the pandemic and the relevance of the palliative care approach in emergency contexts.